A hyperbranched mechanically interlocked rotaxane-type polymer. (16th December 2015) - Bhattacharjee, Susmita; Gong, Caiguo; Jones, Jason W.; Gibson, Harry W.
Abstract: The interaction of the diacid chloride (2 ) of N, N'-bis(5″-carboxypentyl)-4, 4′bipyridnium bis(hexafluorophosphate) (1 ) with m- phenylene-5′-hydroxymethyl-1′, 3′-phenylene-32-crown-10 (3 ) at −70 °C led to the in situ formation of a pseudorotaxane4 as an AB2 monomer, which was allowed to polymerize by raising the temperature and adding a catalytic amount of pyridine. The resulting hyperbranched polymer was held together via mechanical bonds formed by threading of the crown ether units by the bipyridinium (paraquat) moieties. The polymer was initially precipitated into aqueous NH4 PF6 to remove any unreacted, water soluble diacid1 to form5b and then precipitated from DMSO into aqueous NH4 PF6 to remove any pyridinium monoester8 complexed with crown ether units in the polymer, leading to6 . The hyprerbranched polyester was characterized by 1 H NMR and NOESY spectroscopies, FAB and MALDI-TOF mass spectrometry and viscometry. NMR spectroscopy confirmed complete esterification of the crown ether alcohol;5b contained 60% monoesterified paraquat units (8 ) and 40% diester moieties (9 ), while6 contained only 24% monoester moieties, which existed primarily as "focal point" units (10 ), but also as uncomplexed linker units (11 ). A variety of mechanically linked structures containing cyclic units is possible, including17 –19 . Mass spectrometry on6 detected masses up to 16.3 kDa, corresponding to a degree of polymerization of 11 units of the diester repeat unit in17 (and/or isomeric structures). Graphical abstract: Highlights: Crown ether monoalcohol and a 4, 4′-bipyridinium diacid chloride formed a pseudorotaxane in situ at low temperature. Addition of pyridine and increasing temperature led to a mechanically linked hyperbranched polyester. Two components: diester (two macrocycles), monoester (one). Precipitation from DMSO removed any non-polymeric moieties. NMR: macrocycles complex focal point bipyridinium units (acetone); no complexes (DMSO), only mechanically linked moieties. MS confirmed the presence of hyperbranched structures with high molar masses, up to 16.3 kDa.